The Influence Of Hotel Facilities On Service Quality At Hotel Bunda Bukittinggi - Andriani, Rika (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2025)
This study aims to analyze the quality of service at Bunda Bukittinggi hotel in terms of hotel facilities. The population in this study were all employees at Hotel Bunda Bukittinggi, both contract employees and permanent employees, totaling 31 employees. Then the sample in this study was the entire population using the census method, which means that the entire population was sampled. Then test the research instrument with validity test and reliability test. Before the multiple linear regression test is carried out, the classical assumption test is carried out by testing normality, linearity, multicollinearity and so on. From the results of multiple linear regression tests, the results show that hotel facilities have a positive and significant effect on Service Quality at Hotel Bunda Bukittinggi both partially and simultaneously have a positive and significant effect so that all hypotheses proposed can be accepted.  Keywords: Service quality, Facilities, Hotel.